PERBEDAAN PENILAIAN PEMBELI MAKAN SIANG DAN MALAM TERHADAP ATRIBUT RUMAH MAKAN PADANG X, BANDAR LAMPUNG - Putri, Rafika Dila; Hudoyo, Agus; Riantini, Maya (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This study aims to analyze differences between lunch and dinner buyers in assessing importance and performance attributes, differences in importance and performance levels between lunch buyers and dinner buyers, and analyze the attributes that need to be improved and maintained. The method used in this study was a survey method by conducting interviews with 35 lunch buyer respondents and 35 dinner buyer respondents. The samples were determined using a probability sampling technique to randomize table numbers and the analytical method used was the Mann-Whitney Test and Importance Performance Analysis (IPA). Interest and performance attribute ratings by buyers used a Likert scale with a range of 1 to 5. This study showed that there was no significant difference in importance and performance ratings between lunch and dinner buyers' ratings. There are 4 different attributes of the importance and performance of dinner and lunch. There is 1 attribute whose performance needs to be improved and 8 attributes whose performance needs to be maintained. Keywords: attributes, Importance Performance Analysis (IPA), importance and performance, lunch buyers and dinner buyers.